Challenges in the use of natural flavorings and labeling compliance in meat preparations in the Umbria region (central Italy) - Sara Di Bella; Raffaella Branciari; Fausto Scoppetta; Antonella Leo; Naceur M. Haouet; Eleonora Scoccia; Marisa Framboas; Maria Lucia Mercuri; Rossana Roila; David Ranucci; Andrea Valiani (Italian Journal of Food Safety, 2024)
There is an increasing trend among food business operators to use natural flavorings in meat preparation to reduce microbial spoilage and extend the shelf life. The objective of this study was to evaluate the prevalence of the use of natural flavoring mixtures in meat preparation, the possible presence of additives in natural flavorings, and the assessment of any transfer of additives contained in natural flavorings into experimentally prepared beef burgers. Based on a preliminary survey conducted as part of the study, approximately 87% of establishments used natural flavoring mixtures in meat preparation. The same natural mixtures used by local industries were added to minced meat in order to produce experimental hamburgers. Citric acid was found in both natural flavoring mixtures ranging from 1760 mg/kg to 92,731 mg/kg and experimental burgers ranging from 57 mg/kg to 2248 mg/kg. Ascorbic acid was present in all natural flavoring mixtures from 260 mg/kg to 98,858 mg/kg but was recovered in three burgers up to 1075 mg/kg. Acetic acid was found in three flavoring mixtures (range 23,539-77,421 mg/kg) and transferred to three treated burgers (range 3063-3202 mg/kg). Nitrite was never found in hamburgers and only once in a natural flavoring mixture at a dose of 26 mg/kg, whereas nitrate was found in some natural flavoring mixtures up to 788 mg/kg but never in hamburgers. The study has raised some critical issues about the appropriate and conscious use of natural flavorings and the possible inadequate meat preparation labeling in the Umbria region.